Dynamique des dispositifs de paiements pour services environnementaux : les apports de l’analyse des politiques Publiques - Denis Pesche; Cécile Bidaud; Philippe Méral; Jean-François Le Coq; Géraldine Froger; Marie Hrabanski (Développement Durable et Territoires)
Based on case studies from two tropical countries, Costa Rica and Madagascar, this article illustrates the relevance of several public policy analysis frameworks to better understand the emergence of payments for environmental services (PES). Those frameworks address issues that institutional economics, centered on the diversity of institutional arrangements and performance, not really explored. Finally, public policy analysis frameworks provide a better understanding of how the conditions of emergence of PES shape their diversity and, ultimately, their performance.